Cyanobacteria community in two tropical eutrophic reservoirs in northeastern Brazil - Oliveira, Fábio Henrique Portella Corrêa de; Silva, Joanne D’Arc Bezerra da; Costa, Anapaula Nunes Silvestre Fernandes; Ramalho, Waldemir Pimentel; Moreira, César Henrique Pinto; Calazans, Tiago Luiz Santana (Acta Scientiarum. Biological Sciences, 2015)
This study investigated the effect of seasonality on the Cyanobacteria community in two tropical eutrophic reservoirs in northeastern Brazil. Monthly samplings were conducted in the sub-surface of reservoirs. The following abiotic variables were analyzed: apparent color, turbidity, conductivity, alkalinity, calcium, magnesium, sodium, potassium, sulfate, total phosphorous, ammonia, nitrate, nitrite, chlorides, total hardness and chlorophyll-a, according to APHA (2012). Cyanobacteria density was quantified through biomass. Data were analyzed using one-way ANOVA and Redundancy Analysis (RDA). Higher mean values of Cyanobacteria biomass occurred in the dry (9.9mm3 L-1) and rainy (19.0mm3 L-1) season in Jucazinho and Carpina reservoirs, respectively, especially Planktothrix agardhii, Cylindrospermopsis raciborskii and Geiterinema amphibium, which occurred in 100% of the samples. RDA analysis revealed that the variables nitrite, ammonia, conductivity, calcium, sulfate, chlorides and alkalinity influenced most the Cyanobacteria community in both reservoirs. High trophic state index was observed throughout the year. Seasonality affected both biotic and abiotic variables.